Relapsing encephalopathy with cerebellar ataxia are caused by variants involving p.Arg756 in ATP1A3 - Sabouraud, Pascal; Riquet, Audrey; Spitz, Marie-Aude; Deiva, Kumaran; Nevsimalova, Sona; Mignot, Cyril; Lesca, Gaëtan; Bednarek, Nathalie; Doummar, Diane; Pietrement, Christine; Laugel, Vincent (European journal of paediatric neurology, 2019)
Mutations in ATP1A3 lead to different phenotypes having in common acute neurological decompensation episodes triggered by a specific circumstance and followed by sequelae. Alongside Alternating Hemiplegia of Childhood (AHC), Rapid-onset Dystonia Parkinsonism (RDP) and Cerebellar ataxia, Areflexia, Pes cavus, Optic atrophy, Sensorineural hearing loss syndrome (CAPOS), a new Relapsing Encephalopathy with Cerebellar Ataxia (RECA) phenotype was published in 2015. We describe herein eight new pediatric cases. Most of them had no specific history when the first neurological decompensation episode occurred, before the age of 5 years, triggered by fever with severe paralytic hypotonia followed by ataxia with or without abnormal movements. Neurological sequelae with ataxia as the predominant symptom were present after the first episode in three cases and after at least one subsequent relapse in five cases. Five of the eight cases had a familial involvement with one of the two parents affected. The phenotype-genotype correlation is unequivocal with the causal substitution always located at position 756. The pathophysiology of the dysfunctions of the mutated ATPase pump, triggered by fever is unknown. Severe recurrent neurological decompensation episodes triggered by fever, without any metabolic cause, should lead to the sequencing of ATP1A3.
Keywords: recidiva; Humans; genetické asociační studie; Brain Diseases; Cerebellar Ataxia; dítě; Child; Female; mutace; Phenotype; cerebelární ataxie; lidé; Fever; sodíko-draslíková ATPasa; nemoci mozku; horečka; ženské pohlaví; Genetic Association Studies; Male; fenotyp; Adolescent; Recurrence; Sodium-Potassium-Exchanging ATPase; Mutation; mužské pohlaví; mladiství